The Experience of Indonesian Lecturer in International Class Program - Alda Yusnaviza, Fitri Kurniawan, Fatkhul Imron & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This research aims at investigates how the lecturers of Universitas MuhammadiyahSurakarta perceive their experience teaching in international class whose students arefrom different nationalities. The participants were taken by purposive sampling. The datawere collected by semi-structured in depht repeated interview. Two lecturers wereinterviewed who teaching in international program currently. Phenomenologicalmethodology was employed to form descriptive themes.The study revealed two themesrelating to how lectures of Universitas Muhammadiyah Surakarta perceive theirexperience teaching in international class. (a)Heterogenouos studentsâ backgroundcreates welcoming and intelectually stimulating athmosphere in the class (b) In-classand out class interaction foster a multicultural take and give - sharing discussion.Keywords: phenomenology, international class program, Universitas Muhammadiyah Surakarta